Comparative Evaluation of Serum Calcium and Magnesium Level in Preeclamptic and NonPreeclamptic Women in a Tertiary Hospital in Southern Nigeria - DO., Allagoa; OJ., Agbo; CG., Orluwene (European Scientific Journal, ESJ, 2018)
Background: Calcium and magnesium are two micronutrients whose role in the development of preeclampsia has been investigated over the years. There is paucity of studies on the role of serum levels of calcium and magnesium in the development of preeclampsia in south-south Nigeria. Objective: Our study evaluated the serum level of calcium and magnesium in preeclamptic and non preeclamptic women in a Tertiary Hospital in southsouth Nigeria. Methodology: We carried out a comparative study in which 52 preeclamptic and 52 non preeclamptic women, who satisfied the eligibility criteria, were enrolled for the study. Data entry and statistical analysis was done using statistical software (IBM SPSS® for windows version 21.0). Data were analyzed for mean and standard deviation. Comparison of serum levels of elements between the two groups was performed by student t-test, and P value < 0.05 was considered as statistically significant. Results: The serum calcium level was statistically lower in the women who developed preeclampsia compared to those who did not (8.37±0.91 mg/dl vs 9.33±1.15mg/dl, p<0.001). The serum magnesium level was not statistically different between women who had preeclampsia and those who did not (1.79±0.24mg/dl vs 1.88±0.37mg/dl, p = 0.102). The systolic and diastolic blood pressure showed a significant negative correlation with serum calcium level, unlike serum magnesiun level in those that had preeclampsia. Conclusion: This study showed that women who developed preeclampsia demonstrated reduced serum calcium level and no reduction in serum magnesium level. This study support the hypothesis that hypocalcaemia, unlike hypomagnecaemia, is a possible aetiology of preeclampsia.